A case-only study to identify genetic modifiers of breast cancer risk for BRCA1/BRCA2 mutation carriers - Coignard, Juliette; Arndt, Volker; Brenner, Hermann; Burwinkel, Barbara; Chang-Claude, Jenny; Hamann, Ute; Kaaks, Rudolf; Kapoor, Pooja Middha (Nature Communications, 2021)
Breast cancer (BC) risk for BRCA1 and BRCA2 mutation carriers varies by genetic and familial factors. About 50 common variants have been shown to modify BC risk for mutation carriers. All but three, were identified in general population studies. Other mutation carrier-specific susceptibility variants may exist but studies of mutation carriers have so far been underpowered. We conduct a novel case-only genome-wide association study comparing genotype frequencies between 60,212 general population BC cases and 13,007 cases with BRCA1 or BRCA2 mutations. We identify robust novel associations for 2 variants with BC for BRCA1 and 3 for BRCA2 mutation carriers, P < 10−8, at 5 loci, which are not associated with risk in the general population. They include rs60882887 at 11p11.2 where MADD, SP11 and EIF1, genes previously implicated in BC biology, are predicted as potential targets. These findings will contribute towards customising BC polygenic risk scores for BRCA1 and BRCA2 mutation carriers.
Gesehen am 13.04.2021